2015
DOI: 10.1039/c4ra15371e
|View full text |Cite
|
Sign up to set email alerts
|

2-Amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) formation and fate: an example of the coordinate contribution of lipid oxidation and Maillard reaction to the production and elimination of processing-related food toxicants

Abstract: 2-Amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) is produced by reaction of phenylacetaldehyde, the Strecker aldehyde of phenylalanine, with creati(ni)ne in the presence of formaldehyde and ammonia, which are formed in situ. Traditionally, the carbonyls compounds required 10 for the formation of PhIP ring were considered to be produced as a consequence of Maillard reaction between phenylalanine and carbohydrates. This review collects all recent evidences suggesting that lipids can also contribute to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 118 publications
0
28
0
1
Order By: Relevance
“…Guillen and Uriarte reported that linoleic acid is associated with the formation of potentially toxic compounds such as free radicals, aldehydes, and ketones. These reactive oxygen species (ROS), formed by the peroxidation of USFA, can cause decomposition of Amadori compounds and development of intermediates for the formation of Strecker aldehydes, pyrazines, and pyridines in the Maillard reaction, and can eventually contribute to the formation of HCAs . However, it is also known that vegetable oils contain antioxidants such as vitamin E, β ‐carotene and phenolic compounds at different levels .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Guillen and Uriarte reported that linoleic acid is associated with the formation of potentially toxic compounds such as free radicals, aldehydes, and ketones. These reactive oxygen species (ROS), formed by the peroxidation of USFA, can cause decomposition of Amadori compounds and development of intermediates for the formation of Strecker aldehydes, pyrazines, and pyridines in the Maillard reaction, and can eventually contribute to the formation of HCAs . However, it is also known that vegetable oils contain antioxidants such as vitamin E, β ‐carotene and phenolic compounds at different levels .…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds could also inhibit the formation of imidazoquinoxaline‐type HCAs by holding pyrazine cation radicals and some other carbon‐centered radicals, which formed during the Maillard reaction, or by different routes. Phenolic compounds can also bind carbonyl compounds efficiently in the conversion of phenylalanine in Strecker degradation to phenylacetaldehyde, which is an intermediate in the formation of PhIP . On the other hand, it is determined that the formation of PhIP is directly related to the temperature, and at 175–200 °C temperatures, the formation of PhIP is at low levels while at temperatures above 200 °C there are significant increases in PhIP content …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increased concentration was a result of the Maillard reaction during frying process. Pyridine, a Strecker degradation product in Maillard reaction, can form PhIP by reacting with aldehydes and creatinine through free radical mechanism or others (Zamora & Hidalgo, 2015). On the contrary, the addition of black pepper considerably inhibited the formation of PhIP and the maximum inhibition reached 100%.…”
Section: Resultsmentioning
confidence: 99%